Efforts to Raise Community Awareness of the Dangers of Early Child Marriage in Pansor Village - Eliyana, Eliyana; Sapriadi, Sapriadi; Atni, Atni; Risnawati, Risnawati; Sapriai, Hairul Rizka; Rumiadi, Rumiadi; Yartono, Raden (Jurnal Ilmiah Mandala Education (JIME), 2024)
In recent years, early marriages are still common because the couple is not yet mature enough to live in a household, making the family less happy and harmonious and giving birth to a less good generation. This article raises awareness and explains the negative impact of early marriage on individuals and groups in Pansor Village, Kayangan District. Through socialization about the dangers of early childhood marriage carried out in the Pansor Village community, Kayangan District, North Lombok, it is hoped that it can provide awareness to the community about how important this socialization is. This outreach explains the dangers of early marriage which has a negative impact. This activity aims to reduce the phenomenon of early marriage and can be minimized so that it does not harm individuals or youth groups, especially in Pansor Village, Kayangan District, North Lombok Regency.